Tärähdyttävät sankarit New Yorkin maailmannäyttelyssä 1939 : Mieskuoro Finlandia Suomen maakuvan viestijänä - Tilli, Inari (Sibelius-Akatemia, 2023)
At the opening of the Finnish section of the New York World’s Fair on May 4, 1939, the Finlandia Male Chorus performed; the choir had been founded especially for the trip to North America, and in particular for performing at the New York World’s Fair. In addition to general coverage in the press, the choir’s travel plans, its preparations, and the trip itself were followed on many different radio broadcasts. What did Mieskuoro Finlandia want to tell about Finland at the New York World’s Fair in the spring of 1939? How was the choir founded, how did it work towards the goal of its journey, and what did it do afterwards? Answers to these questions are sought here especially through the concepts of cultural diplomacy and country image. According to the article, the Finlandia Male Chorus’ activities serve as a good example of the creation of a country’s image implemented through the means of cultural diplomacy, which also includes cultural propaganda, i.e. the promotion of a country using its culture as a tool. The methodological approach of the article is situated in the cultural and historical research field of music
Keywords: kuorot; historia; mieskuorot; maailmannäyttelyt; Suomi; suomalaiset; New York (kaupunki)